2008
DOI: 10.1021/bi800993c
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies of the Transmembrane C-Terminal Domain of the Amyloid Precursor Protein (APP): Does APP Function as a Cholesterol Sensor?

Abstract: The amyloid precursor protein (APP) is subject to alternative pathways of proteolytic processing, leading either to production of the amyloid-β (Aβ) peptides or to non-amyloidogenic fragments. Here, we report the first structural study of C99, the 99-residue transmembrane C-terminal domain of APP liberated by β-secretase cleavage. We also show that cholesterol, an agent that promotes the amyloidogenic pathway, specifically binds to this protein. C99 was purified into model membranes where it was observed to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
326
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(364 citation statements)
references
References 102 publications
34
326
4
Order By: Relevance
“…The detergent soluble paramagnetic probe 16-DOXYL-stearic acid (DSA) was used to reveal the regions of gp41-M-MAT that interact with the DPC detergent micelle (41)(42)(43). DSA is a paramagnetic probe that localizes to the hydrophobic interior of detergent micelles and membranes where it enhances relaxation of resonances from residues that are in proximity to the micelle or membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The detergent soluble paramagnetic probe 16-DOXYL-stearic acid (DSA) was used to reveal the regions of gp41-M-MAT that interact with the DPC detergent micelle (41)(42)(43). DSA is a paramagnetic probe that localizes to the hydrophobic interior of detergent micelles and membranes where it enhances relaxation of resonances from residues that are in proximity to the micelle or membrane.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the insertion depth and membrane orientation of SpoVM in a lipid bilayer, we used NMR paramagnetic relaxation enhancements (PREs) using a water-soluble probe gadopentetic acid [Gd(DTPA)] and a membrane-soluble probe 16-doxylstearic acid (16-DSA) (36,37). In this technique, amino acid residues accessible by solvent molecules will experience large PRE effects from Gd(DTPA) and small effects from 16-DSA, whereas residues embedded in the membrane will have small PREs from Gd(DTPA) and large effects from 16-DSA.…”
Section: Curvature-dependent Adsorption Through Slight Increases In Bmentioning
confidence: 99%
“…Phosphorylation of APP at Thr 668 Suppresses Lipid Association of Cytoplasmic Terminus of APP-Recent structural studies of the cytoplasmic domain of APP revealed that APP and APP CTFs can interact with the cytoplasmic-membrane region through binding of the APP C-terminal tail (composed of 7 to 9 amino acids) with membrane lipids (42). Because phosphorylation of APP at Thr 668 induces a significant change in its cytoplasmic domain conformation (15,24,25) (supplemental Fig.…”
Section: Phosphorylation State Of App Carboxyl-terminal Fragments At Thrmentioning
confidence: 99%
“…APP-⌬C8 is expected to have an increase in its membrane fluidity as it lacks the interaction between the C-terminal 8 residues and the membrane lipids (42). Therefore, APP-⌬C8 may disperse throughout the membrane instead of staying in a restricted area such as the DRM, which contains the active ␥-secretase.…”
Section: Phosphorylation State Of App Carboxyl-terminal Fragments At Thrmentioning
confidence: 99%